Leisure-time physical activity and self-perception of health status in Colombia (2013)
Introduction: Physical activity is a protective factor for developing chronic diseases. Population surveys provide information on its health status and related factors. The aim of this study was to explore the association between leisure-time physical activity and self-perceived health status, using data from the national survey of the nutritional situation in Colombia, 2005. Material and methods: A cross-sectional analytical study was conducted on 14,601 subjects (18-64 years) from Colombia, selected through complex sampling. We selected variables related to self-perception of health and physical activity, and were categorized according to the international physical activity questionnaire's recommendations. Results: A logistic regression analysis identified increased risk in women who reported low levels of physical activity and perceived their health as poor, compared with high physical activity (adjusted OR = 1.92; 95%CI, 1.19-3,10). In men no such evidence was found (adjusted OR = 0.80; 95%CI, 0.62 to 1.03). Women and men with a low educational level, and men without access to the health system more often perceived their health as fair or poor. Conclusions: A vigorous level of leisure-time physical activity and good self-perceived health status were significantly associated in women, whereas in men this association was not found. Good health assessments were also associated with higher educational levels in both women and men, and with having access to the health system in men. These results suggest the need to address public policy towards promotion of physical activity, and ensuring access to education and the health system. © 2011 Consell Català de l'Esport. Generalitat de Catalunya.